2021
DOI: 10.1186/s40798-021-00343-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cardiorespiratory Fitness and Circulating Proteins in 50-Year-Old Swedish Men and Women: a Cross-Sectional Study

Abstract: Background and Aims A strong cardiorespiratory fitness is suggested to have beneficial effects on cardiovascular risk; the exact mechanisms underlying the cardioprotective effects of fitness remain uncertain. Our aim was to investigate associations between cardiorespiratory fitness and multiple plasma proteins, in order to obtain insights about physiological pathways associated with the effects of exercise on cardiovascular health. Methods In the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(130 reference statements)
2
2
0
Order By: Relevance
“…In accordance with observational data derived from the literature, we found that higher chronic levels in PA were associated with lower GDF‐15 concentrations. These results are consistent with studies demonstrating that resting levels in GDF‐15 are inversely related with both long‐term PA 20 and cardiorespiratory fitness 21 . These findings also support the role of PA in preventing biological aging, because GDF‐15 has been associated with several hallmarks of aging that can be modulated through PA 40 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with observational data derived from the literature, we found that higher chronic levels in PA were associated with lower GDF‐15 concentrations. These results are consistent with studies demonstrating that resting levels in GDF‐15 are inversely related with both long‐term PA 20 and cardiorespiratory fitness 21 . These findings also support the role of PA in preventing biological aging, because GDF‐15 has been associated with several hallmarks of aging that can be modulated through PA 40 .…”
Section: Discussionsupporting
confidence: 90%
“…GDF-15 are inversely related with both long-term PA 20 and cardiorespiratory fitness. 21 These findings also support the role of PA in preventing biological aging, because GDF-15 has been associated with several hallmarks of aging that can be modulated through PA. 40 These include telomere attrition, 15 the senescence-associated secretory phenotype (SASP) and mitochondrial dysfunction. In contrast, it has been reported that acute physical exercise 18 and short-term exercise training 19 induce a raise in GDF-15 concentrations, suggesting that PA may exert distinct short-term and long-term effects on GDF-15, as it does on other exerkines such as IL-6, for instance.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Data from several studies have identified multiple proteins that are associated with HF as well as HF prognosis ( 10 , 11 ). However, while there are data on the association between physical activity and plasma proteins that are associated with cardiovascular disease, they are currently limited in HF populations ( 12 , 13 ). Furthermore, while the role of physical activity as a predictor of mortality and hospitalization has been previously studied, it has oftentimes not specifically studied patients hospitalized for HF.…”
Section: Introductionmentioning
confidence: 99%